THE BURMESE CINNAMOMUM (LAURACEAE)*) - A.J.G.H. KOSTERMANS (REINWARDTIA, 1998)
The Burmese species of Cinnamomutn are revised and 11 speciesare recognized. Out of these eight new species are described for the first time.